2021
DOI: 10.3390/genes12101513
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Neurological Phenotype of Ring Chromosome 10 Syndrome: A Case Report and Review of the Literature

Abstract: Ring chromosome 10 [r(10)] syndrome is a rare genetic condition, currently described in the medical literature in a small number of case report studies. Typical clinical features include microcephaly, short stature, facial dysmorphisms, ophthalmologic abnormalities and genitourinary malformations. We report a novel case of r(10) syndrome and review the neurological and neuroradiological phenotypes of the previously described cases. Our patient, a 3 year old Italian girl, represents the 20th case of r(10) syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Therefore, for the purpose of this study, 50-day old (pre-symptomatic) and 100-day old animals (post-symptomatic) were classified into respective groups, to represent stages of the disease. Among the aberrantly spliced genes, zinc finger, MYND typecontaining 11 ( Zmynd11 ) is of particular interest due to its recent implications in autism-related motor delay (Moskowitz, Belnap et al 2016); intellectual disability (Pruccoli, Graziano et al 2021) and brain atrophy and ataxia (Indelicato, Zech et al 2022). In addition, Zmynd11/ZMYND11 has been previously reported to be an RNA binding partner of TDP-43 in the mouse brain (Narayanan, Mangelsdorf et al 2013), rat cortical neurons (Sephton, Cenik et al 2010) and post-mortem human brain (Tollervey, Curk et al 2011) and was reported to be aberrantly spliced in the spinal cord of sporadic ALS patients with TDP-43 pathology (Rabin, Kim et al 2010).…”
Section: Descriptionmentioning
confidence: 99%
“…Therefore, for the purpose of this study, 50-day old (pre-symptomatic) and 100-day old animals (post-symptomatic) were classified into respective groups, to represent stages of the disease. Among the aberrantly spliced genes, zinc finger, MYND typecontaining 11 ( Zmynd11 ) is of particular interest due to its recent implications in autism-related motor delay (Moskowitz, Belnap et al 2016); intellectual disability (Pruccoli, Graziano et al 2021) and brain atrophy and ataxia (Indelicato, Zech et al 2022). In addition, Zmynd11/ZMYND11 has been previously reported to be an RNA binding partner of TDP-43 in the mouse brain (Narayanan, Mangelsdorf et al 2013), rat cortical neurons (Sephton, Cenik et al 2010) and post-mortem human brain (Tollervey, Curk et al 2011) and was reported to be aberrantly spliced in the spinal cord of sporadic ALS patients with TDP-43 pathology (Rabin, Kim et al 2010).…”
Section: Descriptionmentioning
confidence: 99%